Relationships between internal and external training load in team-sport athletes: Evidence for an individualized approach - Bartlett, J. D.; O`Connor, F.; Pitchford, N.; Torres-Ronda, L.; Robertson, S. J. (International Journal of Sports Physiology and Performance, 2017)
Purpose: The aim of this study was to quantify and predict relationships between rating of perceived exertion (RPE) and GPS training-load (TL) variables in professional Australian football (AF) players using group and individualized modeling approaches.